Moral distress in frontline healthcare workers in the initial epicenter of the COVID‐19 pandemic in the United States: Relationship to PTSD symptoms, burnout, and psychosocial functioning. Issue 10 (22nd July 2021) - Norman, Sonya B.; Feingold, Jordyn H.; Kaye‐Kauderer, Halley; Kaplan, Carly A.; Hurtado, Alicia; Kachadourian, Lorig; Feder, Adriana; Murrough, James W.; Charney, Dennis; Southwick, Steven M.; Ripp, Jonathan; Peccoralo, Lauren; et al.
Abstract: Introduction: Little is known about the relationship between moral distress and mental health problems. We examined moral distress in 2579 frontline healthcare workers (FHCWs) caring for coronavirus disease 2019 (COVID‐19) patients during the height of the spring 2020 pandemic surge in New York City. The goals of the study were to identify common dimensions of COVID‐19 moral distress; and to examine the relationship between moral distress, and positive screen for COVID‐19‐related posttraumatic stress disorder (PTSD) symptoms, burnout, and work and interpersonal functional difficulties. Method: Data were collected in spring 2020, through an anonymous survey delivered to a purposively‐selected sample of 6026 FHCWs at Mount Sinai Hospital; 2579 endorsed treating COVID‐19 patients and provided complete survey responses. Physicians, house staff, nurses, physician assistants, social workers, chaplains, and clinical dietitians comprised the sample. Results: The majority of the sample (52.7%–87.8%) endorsed moral distress. Factor analyses revealed three dimensions of COVID‐19 moral distress: negative impact on family, fear of infecting others, and work‐related concerns. All three factors were significantly associated with severity and positive screen for COVID‐19‐related PTSD symptoms, burnout, and work and interpersonal difficulties. Relative importance analyses revealed that concerns about work competencies and personal relationships were most strongly related to all outcomes. Conclusion: Moral distress is prevalent in FHCWs and includes family‐, infection‐, and work‐related concerns. Prevention and treatment efforts to address moral distress during the acute phase of potentially morally injurious events may help mitigate risk for PTSD, burnout, and functional difficulties.